Synthesis and analgesic activity evaluation of derivatives of 2-[(1,4-dioxo-1-amino-4-arylbutyl-2-en-2-yl)amino]-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylic acid - Alena I. Siutkina; Ramiz R. Makhmudov; Daria A. Shipilovskikh (Chimica Techno Acta)
The synthesis of new derivatives of 2-[(1,4-dioxo-1-amino-4-arylbutyl-2-en-2-yl)amino]-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylic acid is described. Starting 2-{[5-aryl-2-oxofuran-3(2H)-ylidene]amino}thiophene-3-carboxylic acids were obtained by intramolecular cyclisation of substituted 4-aryl-4-oxo-2-thienylaminobut-2-enoic acids in acetic anhydride. New derivatives of 2-[(1,4-dioxo-1-amino-4-arylbutyl-2-en-2-yl)amino]-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylic acids were obtained via decyclization reaction of 2-{[5-aryl-2-oxofuran-3(2H)-ylidene]amino}thiophene-3-carboxylic acids. The structure of the compounds obtained was confirmed by the 1H and 13C NMR spectroscopy, IR spectrometry and elemental analysis methods. Analgesic activity of new compounds has been studied by the “hot plate” method on outbred white mice of both sexes with intraperitoneal injection. It was found that derivatives of 2-[(1,4-dioxo-1-amino-4-arylbutyl-2-en-2-yl)amino]-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylic acid possess analgesic effect exceeding the effect of the comparison drug metamizole.